Novel concentrated water-in-oil emulsions based on a non-ionic silicone surfactant: Appealing application properties and tuneable viscoelasticity - Binder, Lisa; Jatschka, Johannes; Baurecht, Dieter; Wirth, Michael; Valenta, Claudia (European journal of pharmaceutics and biopharmaceutics, 2017)
[Display omitted] •The potential of a silicone emulsifier as a stabiliser for skin-friendly water-in-oil emulsions was demonstrated.•Highly stable water-in-oil emulsions with desirable application properties were developed.•A dependency of the viscoelasticity on the formulation composition was found.•Permeation of a hydrophilic model drug through the stratum corneum was promoted.•Skin penetration determined by ATR-FTIR of the silicone additive was negligible. Silicone excipients are non-irritating ingredients that are extensively used in topical formulations. In the present study, innovative water-in-oil emulsions with a high water content stabilised by a non-ionic silicone surfactant were developed. Effects of formulation composition on its properties and stability were investigated. It was possible to prepare highly stable emulsions with a water volume fraction of up to 80%. The emulsions exhibited desirable application properties such as non-sticky and cooling qualities. A dependency of the viscosity on the water fraction was found; this offers the opportunity to create emulsions with fine-tuned rheological properties. Furthermore, it could be shown in skin studies that the in vitro release of a hydrophilic model drug is influenced by the configuration of the oil phase. The penetration of the silicone surfactant and the other deployed additives was monitored using combined tape stripping and ATR-FTIR experiments, revealing that the compounds remain in the superficial layers of the stratum corneum, thus minimising the risk for skin irritation.